Addressing Supply Chain Issues through CSR: Leveraging Competitive Advantage in Indonesian Insurance Sector - Ronaldo, Reza; Yulmaulini, Yulmaulini; Fadoli, Fadoli (International Journal of Supply Chain Management, 2018)
The current research investigates the empirical debate in order to addressing the supply chain management issues through corporate social responsibilities and further help the company to get the competitive advantage among competitors. The results suggested that all corporate social responsibilities variables (code of ethics, environmental orientation and community welfare) have a negative and significant impact on reducing supply chain issues (which includes cost management issue, quality management issues and relationship management issues) and then further reducing these supply chain management issues also help to enhance the competitive advantage of the firm. Therefore it can be recommended that these corporate social indicators are very helpful in reducing supply chain issues.